2015
DOI: 10.1016/j.ajog.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Trends in gestational weight gain: the Pregnancy Risk Assessment Monitoring System, 2000–2009

Abstract: OBJECTIVE Achieving adequate gestational weight gain (GWG) is important for optimal health of the infant and mother. We estimate current population-based trends of GWG. STUDY DESIGN We analyzed data from the Pregnancy Risk Assessment Monitoring System for 124,348 women who delivered live infants in 14 states during 2000 through 2009. We examined prevalence and trends in GWG in pounds as a continuous variable, and within 1990 Institute of Medicine (IOM) recommendations (yes/no) as a dichotomous variable. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 24 publications
10
63
0
2
Order By: Relevance
“…Excessive GWG was more prevalent than inadequate or appropriate GWG in every state; in 17 states, the prevalence of excessive GWG was ≥50%. Other studies have reported similar findings (2) and indicate that during the past decade, the prevalence of excessive GWG has increased and prevalence of inadequate GWG has remained stable (3). These findings indicate that effective interventions during pregnancy, in addition to routine prenatal care, are needed to promote appropriate GWG.…”
Section: Discussionsupporting
confidence: 58%
“…Excessive GWG was more prevalent than inadequate or appropriate GWG in every state; in 17 states, the prevalence of excessive GWG was ≥50%. Other studies have reported similar findings (2) and indicate that during the past decade, the prevalence of excessive GWG has increased and prevalence of inadequate GWG has remained stable (3). These findings indicate that effective interventions during pregnancy, in addition to routine prenatal care, are needed to promote appropriate GWG.…”
Section: Discussionsupporting
confidence: 58%
“…In a recent analysis of the Pregnancy Risk Assessment Monitoring System (PRAMS) 2010-2011, 21%, 32%, and 47% of women reported having inadequate weight gain, adequate weight gain, and excessive weight gain during pregnancy, respectively (38). In PRAMS, underweight women and normal weight women had decreased odds versus excessive weight gain, while overweight and obese women had increased odds of excessive weight gain (38, 39). Similar patterns were observed in our cohort of SLE women, with the frequency of excessive weight gain lower in normal weight and underweight women than overweight and obese women.…”
Section: Discussionmentioning
confidence: 98%
“…2, 4, 5 Long-term changes in GWG patterns would require more time following IOM’s issuance of guidelines; however, raising awareness among expecting mothers and obstetric care providers is critical to yield substantial changes. In 2013, the IOM and American College of Obstetrics and Gynecology support the dissemination of the GWG guidelines and implementation at the practitioner level, and it is anticipated that GWG goal setting and nutrition and exercise consultation by practitioners will help gradually reduce GWG among overweight and obese women in the next few years.…”
Section: Commentmentioning
confidence: 99%
“…1 The trend of GWG by BMI in statewide or nationwide data has not been available, particularly after 2009, although GWG trend from 2000–2009 in the Pregnancy Risk Assessment Monitoring System has been reported. 2 Categorization of GWG within or outside of the BMI-specific guidelines by total GWG only without consideration of gestational age may induce bias for pregnancies shorter or longer than 40 weeks, thus weekly GWG in the 2 nd and 3 rd trimesters needs to be factored into the determination. 3 GWG below the guidelines has been associated with small for gestational-age (SGA), while GWG above the guidelines has been linked to large-for-gestational-age (LGA) and macrosomia.…”
mentioning
confidence: 99%